FABP4 mediates endoplasmic reticulum stress and autophagy to regulate endometrial epithelial cell function during early sheep gestation - Meijun SONG; Kexing HAO; Fenghua QI; Wenjuan ZHAO; Zhengrong WANG; Jing WANG; Guangdong HU (The Society for Reproduction and Development, 2023)
Dynamic changes in the endometrium are crucial for establishing early pregnancy in ruminants. Blastocyst elongation and implantation require hormones and nutrients to be secreted from the maternal endometrium. The fatty acid-binding protein FABP4 is a widely expressed fatty acid transport protein that promotes cell proliferation, migration, and invasion and is involved in conceptus implantation. However, the mechanism underlying the functional regulation of endometrial epithelial cells (EECs) by FABP4 during ovine peri-implantation remains unclear. We simulated hormonal changes in vitro in sheep EECs (SEECs) during the peri-implantation period and found that it elevated FABP4 expression. FABP4 inhibition significantly reduced cell migration, endoplasmic reticulum stress, and autophagy, suggesting that FABP4 regulates endometrial function in sheep. Moreover, the FABP4 inhibitor BMS309403 counteracted hormone-mediated functional changes in SEECs, and an endoplasmic reticulum stress activator and autophagy inhibitor reversed the abnormal secretion of prostaglandins induced by FABP4 inhibition. These results suggest that FABP4 affects ovine endometrial function during early gestation by regulating endoplasmic reticulum stress and autophagy in SEECs.